Correlation Between Cryptococcus Infection and the Nasal Mycobiota in a Population of Free-Ranging Koalas (Phascolarctos cinereus) in New South Wales, Australia - Andrew S. McPherson; Sophie L. Haworth; Alex Kan; Luisa Monteiro de Miranda; Mark B. Krockenberger (Journal of Fungi)
Cryptococcosis is a fungal disease in humans and animals, caused by the Cryptococcus neoformans and Cryptococcus gattii species complexes. Clinical cryptococcosis primarily manifests as upper respiratory tract disease; however, dissemination to other organs, particularly the brain, can occur. Nasal colonisation and subclinical cryptococcosis are common in koalas (Phascolarctos cinereus) due to their shared environmental niche with Cryptococcus: Eucalyptus trees. However, for reasons that remain unclear, the prevalence of clinical disease is low in koalas. Interactions between respiratory pathogens and the nasal mycobiome are thought to play a role in the development and progression of numerous respiratory diseases. As such, this study aimed to characterise the mycobiome of the nasal vestibule in koalas with and without evidence of cryptococcal colonisation and subclinical disease via the next-generation sequencing (NGS) of the ITS1 region of the fungal internal transcribed spacer (ITS) gene. Samples were collected from 47 koalas from a population of free-ranging koalas in the Liverpool Plains, NSW, Australia, with a known history of Cryptococcus exposure and nasal colonisation. Of the 47 animals tested, 6.4% were culture-positive only, 4.3% were seropositive only, and 2.1% were culture- and seropositive. C. gattii was detected in four samples via NGS. C. neoformans was not detected via NGS. There were no significant differences in the nasal mycobiomes of Cryptococcus-positive and -negative animals; thus, we could not establish a definitive association between the mycobiome and infection outcomes. We identified a number of fungal genera that were significantly more abundant in samples from Cryptococcus-positive animals, but there was no apparent relationship between these genera and the development of cryptococcosis. This study represents the first investigation of the nasal mycobiota of wild koalas. Further studies involving koalas with clinical disease are necessary to determine the role of the nasal mycobiota in the development of cryptococcosis.